Introduction to personality study - "Cattell, Raymond B." (New York, 1950)
Originally published in 1950, the need for a small standard text on basic principles of personality structure and development had been very apparent to teachers of psychology for some time. There were many books illustrating specialized or applied aspects of the psychology of personality - such as abnormal psychology, educational psychology, child psychology, mental measurement, vocational guidance, etc. - but lacking was a treatment of personality study as pure psychology, concentrating on the fundamentals. The aim of this title was therefore to bring the general problems of personality description and development, normal and abnormal, into a single perspective and to integrate the principle fields of observation in clear cut generalizations.
Keywords: Psychology